THE UNIQUENESS OF THE CULTURE OF THE AFRICAN PEOPLE (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
The end of the 15th century, various fields of culture flourished in the Ottoman society. A number of talented poets such as poetess Mehri Khotun and poet Mulla Mahmud have grown up in the country. Turkish architecture grew using the experience of master-builders brought from different countries. The wonderful architectural masterpieces built by Khoja Sinon, who is a Greek, made him known to the whole world. During his career, he led the construction of more than 300 structures: mosques, madrasas, palaces, fountains, baths, and bridges. The development of geography among various fields of science is particularly noteworthy.